Implicit affectivity in clinically depressed patients during acute illness and recovery - Thomas Suslow (BMC Psychiatry, 2019)
Abstract Background Clinical depression is characterized by high levels of negative affect (NA) and attenuated positive affect (PA). Psychological and pharmacological treatments have been shown to reduce NA and to enhance PA in depressed patients. Following dual-process models, two types of affect can be distinguished: explicit (or self-reported) affect, which is formed by conscious reflections, and implicit affect, which relates to automatic affective reactions. The present study was conducted to examine, for the first time, both implicit and explicit affectivity in patients suffering from acute depression. Moreover, changes in patients’ implicit and explicit affectivity were investigated over the course of inpatient treatment. Methods Thirty-nine patients suffering from major depression and 39 healthy individuals participated in the study. Implicit affectivity was assessed using the Implicit Positive and Negative Affect Test. The explicit state and trait affectivity were measured by the Positive and Negative Affect Schedule. The level of depressive symptoms was assessed with the Beck Depression Inventory. Tests were administered to patients after admission and after 7 weeks of therapy, whereas healthy controls were investigated only once. We examined whether either comorbidity or antidepressant medication has an effect on affectivity. Results Patients with acute depression had lower implicit and explicit PA scores and higher implicit and explicit NA scores than the healthy controls. After treatment, patients’ level of depression decreased significantly. At posttreatment, patients exhibited heightened implicit and explicit PA and diminished explicit trait NA. Independent of antidepressant medication and comorbidity, no significant change in implicit NA was observed over the course of treatment. Implicit NA was correlated with explicit NA in acute depression but not during recovery. Conclusions Acute depression appears to be characterized by decreased implicit and explicit PA and increased implicit and explicit NA. After 7 weeks of treatment, depressed patients’ implicit and explicit PA increased, and explicit trait NA decreased. No decrease in implicit NA and explicit state NA occurred over the course of treatment. Finally, it seems that in the state of acute depression, the interplay between the automatic and reflective systems could be increased for negative affectivity.